Lesion Location and Possible Etiology of Acute Unilateral Vestibulopathy - Zhang M; Wang J; Xue S; Liu S; Li K; Zhao T; Feng Y; Sui R; Yang B; Yang X (International Journal of General Medicine)
Menglu Zhang,1,2,* Jianrong Wang,1,2,* Siru Xue,1 Shui Liu,3 Kangzhi Li,4 Tongtong Zhao,1,2 Yufei Feng,1,2 Rubo Sui,2 Bentao Yang,5 Xu Yang1 1Department of Neurology, Aerospace Center Hospital, Peking University Aerospace School of Clinical Medicine, Beijing, 100049, People’s Republic of China; 2Department of Neurology, The First Affiliated Hospital of Jinzhou Medical University, Jinzhou, 121001, People’s Republic of China; 3Department of Radiology, Aerospace Center Hospital, Peking University Aerospace School of Clinical Medicine, Beijing, 100049, People’s Republic of China; 4Department of Neurology, Peking University Shougang Hospital, Beijing, 100144, People’s Republic of China; 5Department of Radiology, Beijing Tongren Hospital, Capital Medical University, Beijing, 100730, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xu Yang, Department of Neurology, Aerospace Center Hospital, Peking University Aerospace School of Clinical Medicine, 15 Yuquan Road, Haidian District, Beijing, 100049, People’s Republic of China, Tel +86010-59971978, Email yangxu2011@163.com Bentao Yang, Department of Radiology, Beijing Tongren Hospital, Capital Medical University, No. 1, Dongjiaomin Lane, Dongcheng District, Beijing, 100730, People’s Republic of China, Tel +86 13671281401, Email cjr.yangbentao@vip.163.comObjective: Acute unilateral vestibulopathy (AUVP) is quite common in clinical practice, but lesion localization and etiological diagnosis of AUVP remain the current clinical challenges, and have always been the focus for researchers. The study aimed to explore the lesion site and possible etiology of AUVP.Methods: This study is a retrospective study. Twenty-three AUVP patients who attended the neurology outpatient clinics of our hospital from January 2020 to March 2022 were included. Clinical data of patients including baseline data, cardiovascular risk factors, immunological test results and infection indicators were collected. Vestibular function tests, including video head impulse test (vHIT), caloric testing, vestibular evoked myogenic potentials (VEMPs) and post-contrast delayed 3D-FLAIR MRI, were performed.Results: Among 32 AUVP patients included, there were 10 males and 13 females, with a male-to-female ratio of 1:1.3, and an average age of 42.13 ± 14.57 years (range 19– 76 years old). Acute persistent vertigo and relapsing-remitting vertigo accounted for 39.1% (9/23) and 60.9% (14/23) of the patients, respectively. Possible etiologies included cardiovascular risk factors (n = 11), abnormal immunological indicators (n = 8), and evidence of infection (n = 3). About 57.1% (12/21) of the patients showed abnormal vHIT (including reduced gain in horizontal canal (HC) in 14.3%, anterior canal (AC) in 4.8%, both the AC and HC in 19%, both the HC and posterior canal (PC) in 14.3%, and all three canals in 9.5% of cases). Probable entire vestibular nerve damage was found in 38.1% of the patients, only 9.5% of the patients followed the innervation pattern of the entire vestibular nerve, these patients had abnormal vHIT and VEMP results, and were considered to have definite entire vestibular nerve damage. Probable superior vestibular nerve (SVN) damage was found in 47.6% of the patients, but only 4.8% (1/21) of the patients followed the innervation pattern of SVN, with reduced VOR gains for AC and HC and abnormal oVEMP results, and were considered to have definite SVN damage. 3D-FLAIR MRI revealed high signal intensity in the SVN and vestibule in 4.8% (1/21) and 19% (4/21) of the patients, respectively.Conclusion: The majority of AUVP patients had a relapsing-remitting course and had vestibular function test results that did not follow the innervation pattern of the vestibular nerve. Post-contrast delayed 3D-FLAIR MRI revealed damage to the vestibule in some patients, suggesting that damage to the labyrinth itself in AUVP deserves clinical attention. The majority of the AUVP patients had cardiovascular risk factors and abnormal systemic immunological indicators, which might be the possible etiologies of AUVP.Keywords: acute unilateral peripheral vestibular dysfunction, etiology, vestibule, labyrinth, vestibular nerve